2002
DOI: 10.1023/a:1025312603880
|View full text |Cite
|
Sign up to set email alerts
|

Congenital heart defects: 15 years of experience of the Emilia-Romagna Registry (Italy)

Abstract: The study has provided epidemiological data for public health surveillance of congenital heart defects in the Emilia-Romagna region. The creation of a system for the nationwide recording of congenital heart defects designed with regard to the sources of ascertainment, the diagnostic criteria, and the system of classification is emphasised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
69
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 34 publications
13
69
1
1
Order By: Relevance
“…2,3 Several large population-based studies estimate the prevalence of CVMs to range from 3 to 6 cases per 1000 live births. [4][5][6] The birth prevalence for severe CVMs in other studies is reported to be B1.5 cases per 1000 live births. 7,8 Despite a wealth of information on the developmental pathways that operate during normal cardiogenesis, only a limited number of genes have been identified in which disease-causing mutations are associated with CVMs.…”
Section: Introductionmentioning
confidence: 89%
“…2,3 Several large population-based studies estimate the prevalence of CVMs to range from 3 to 6 cases per 1000 live births. [4][5][6] The birth prevalence for severe CVMs in other studies is reported to be B1.5 cases per 1000 live births. 7,8 Despite a wealth of information on the developmental pathways that operate during normal cardiogenesis, only a limited number of genes have been identified in which disease-causing mutations are associated with CVMs.…”
Section: Introductionmentioning
confidence: 89%
“…The rate of smokers in the mothers of cases with VSD was also higher than in the mothers of 2,640 malformed controls (22.2 %) visited at home (OR with 95% CI: 1.6, 1.2-2.1) but this difference was more obvious in regular/ The birth outcomes of newborn infants in the subgroups of cases and all controls born to mothers visited at home were evaluated according to smoking during the study pregnancy. Mean gestational age (39.1 wk) was similar in 68 case mothers with smoking and 152 case mother without smoking, however, mean birth weight was lower in the newborns of smoker case mothers (2,960 g) than in the newborns of non-smoker case mothers (3,066). The mean gestational age was 39.3 wk and 39.4 wk in the newborns of 152 control mothers who smoked during the study pregnancy and 648 control mothers who did not smoke, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…congenital cardiovascularis abnormalities (CCVAs) are the most frequent CA-group. The birth prevalence of cases with CCVA was between 4 and 50 per 1000 live-births in different studies because their occurrence is dependent on the age at examination and the sensitivity of the examination technique, the case definition and the types of cases included in the studies [1][2][3][4][5]. A Hungarian population-based study of 2,259 children based on the pediatric cardiologic examination and/or the evaluation of autopsy report of each individual child, the birth prevalence of CCVAs was 10.2 per 1000 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a literature review, only two publications in English language were found with similar goal to our study, that was to evaluate presence of abdominal malformations in patients with CHD through AUS 9,10 . In contrast, our study is unique in that all CHD patients underwent AUS, high resolution karyotype and FISH for detection of microdeletion 22q11.2, and all were examined by a clinical geneticist 7,[8][9][10][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%